Grüss-Type Inequalities Involving Bounds Constant via Analytic Kernel Fractional Integral (Contemporary Mathematics, 2025)
The primary aim of this study is to derive a generalization of certain Grüss-type inequalities under constant constraints via a generalized Analytical kernel Riemann-Liouville fractional integral. We derived new Grüss-type inequalities with constant limits using generalized fractional integral operators with identical and varying parameters. The results acquired are more broadly applicable.
Keywords: Grüss type inequalities; Riemann-Liouville fractional integral; Analytic kernel fractional integral